Co-doped ZnO–PVA Nanocomposite for EMI Shielding. (22nd January 2016) - Singh, Hema; Kumar, Deepak; Sawant, Kailas K.; Devunuri, Nagaraju; Banerjee, Shaibal
ABSTRACT: The article describes the mechanical properties and electromagnetic shielding of Co-doped ZnO–poly(vinyl alcohol) nanocomposite. Significant improvements in mechanical properties can be obtained by incorporating inorganic nano fillers. The E-modulus and tensile strength were found to be enhanced with the increase in the doping concentration of Co.05 Zn.95 O incorporated in PVA matrix. Further, we have observed that electromagnetic shielding of the composite filled with 2 wt% concentration of Co.05 Zn.95 O in the PVA matrix exhibited utmost reflection loss of − 47.31 dB in the bandwidth 8–12 GHz which may be attributed to good compatibility of dielectric and magnetic properties of materials. GRAPHICAL ABSTRACT: